2020
DOI: 10.1007/s10530-020-02421-3
|View full text |Cite
|
Sign up to set email alerts
|

A perfect storm: ploidy and preadaptation facilitate Saccharum spontaneum escape and invasion in the Republic of Panama

Abstract: Polyploidy may contribute to invasive ability as it can lead to high survival and fitness during establishment and enhance the processes of adaptation to novel environments by increasing genetic diversity in invading propagules. Many grasses are polyploid and many are aggressive invaders, making them persistent problems in disturbed environments worldwide. Today, vast areas of central Panama are dominated by Saccharum spontaneum, a perennial grass that originates from Asia. While widely regarded as invasive, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In summary, we found that nutrient addition increased the growth of Saccharum spontaneum, but these effects varied seasonally and differed between biomass and density responses. Given the substantial impacts of S. spontaneum within the Panama Canal Watershed [24] and in many other parts of the world where it is a weedy invader [45], there is a great need to understand the management activities that help suppress, or unintentionally promote, its growth. This study highlights a potential risk of fertilizer applications during restoration, agriculture, agroforestry, or other activities in which S. spontaneum invasion is a challenge to land management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, we found that nutrient addition increased the growth of Saccharum spontaneum, but these effects varied seasonally and differed between biomass and density responses. Given the substantial impacts of S. spontaneum within the Panama Canal Watershed [24] and in many other parts of the world where it is a weedy invader [45], there is a great need to understand the management activities that help suppress, or unintentionally promote, its growth. This study highlights a potential risk of fertilizer applications during restoration, agriculture, agroforestry, or other activities in which S. spontaneum invasion is a challenge to land management.…”
Section: Discussionmentioning
confidence: 99%
“…It is adapted to drought, burns frequently, and is difficult to eradicate, which is why it is considered one of the most serious weeds where it occurs [18,23]. S. spontaneum was most likely introduced to the Republic of Panamá in 1939 with a United States Department of Agriculture (USDA) germplasm collection for sugarcane [24] and by the 1960s, had spread widely through disturbed areas [25]. Control of S. spontaneum is actively pursued throughout the country and is especially important in the watershed of the Panama Canal, where S. spontaneum is widespread and persistent [24,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many nonnative and invasive grasses can quickly establish and persist asexually by rhizomatous reproduction and local spread, their ability to flourish and become widespread in new locations may depend on sexual reproduction and influx of novel genetic variation from other populations or species. Gene flow among introduced lineages and subsequent selection in new environments may have facilitated success of several established perennial grass invaders including Bromus tectorum (Novak and Mack, 1993 ) and Imperata cylindrica (Lucardi et al, 2014 ) throughout the United States and Saccharum spontaneum (Saltonstall et al, 2021 ) in Panama (Figure 1 ). These species have all had incredibly damaging impacts by altering fire regimes and displacing native communities in their invaded ranges (Hooper et al, 2005 ; Fusco et al, 2019 ).…”
mentioning
confidence: 99%